The Digital Divide in Online Learning: A Case Study of University Students in Nepal (Prithvi Academic Journal, 2022)
This article analyses the online teaching-learning experience of university teachers and students during the COVID-19 pandemic in Nepal. The purpose of this study is to explore the challenges of online teaching-learning such as the availability of ICT infrastructure, technological skills and management for online classes by the higher education institutions. The researcher collected and studied some of the related academic and policy documents to understand the procedure of online teaching and learning in and around the country during the pandemic. This study was based on qualitative research utilizing semi-structured interviews with 15 participant students and five teachers from Prithvi Narayan Campus, Pokhara, Nepal. Only the students of the Faculty of Humanities and Social Sciences, and the Faculty of Management were selected for data collection. This study took the non-participant observation of various online classes and personal involvement and experiences as references to support and strengthen the data collected through interviews. The purpose was to find and discover the situation of online modes of teaching learning. The findings of the study indicated that the digital use in teaching and learning is the best alternative as it creates opportunities in an adverse situation. However, it causes many divisions among students. It is suggested that the government and university authorities should create a strong-learning atmosphere among the students so that the lines of division among students would be erased gradually.